Анализ номенклатуры сварных конструкций с крепежными элементами – типа приварок и состояния технологической оснащенности сборочно-сварных операций по установке приварок - Астафьева, А. А.; Обозин, Я. В.; Шевченко, И. А. (My University, 2020)
In this thesis, an analysis of the literature data is made, on the basis of which the types of assembly and welding equipment and the basis for creating an automated complex for installing, fixing and grabbing bonks in the body of special items were considered. The analysis showed that the most significant are the costs of designing and manufacturing special devices. It follows from this that it is necessary to reduce costs and increase productivity by automating this complex.
Keywords: сварные конструкции; сборочно-сварная операция; приварка